A study of influence of interference phenomenon on stagger spinning of thin-walled tube. (December 2015) - Ge, Ting; Wang, Jin; Lu, Guo-Dong; Pan, Guo-Jun
In this article, a unique phenomenon called position and inclination interference in stagger spinning process is characterized and investigated. A series of trials are presented to illustrate the causality of visible bulge and concave of wall thickness between position interference, as well as the imbalance and oscillation of roller force. Also, effects of inclination interference have been discussed. Finally, formulae of roller interval selection without interference phenomenon are derived based on the characteristics of position and inclination interference to help exclude invalid combination of roller intervals and guide selection of inclination of roller and blank, which will effectively reduce the amounts of invalid experiments or simulations.